Sleep-wake patterns of student workers and non-workers - Vinha, D.; Cavalcante, J. A.; Andrade, MMM (Swets Zeitlinger Publishers, 2002)
Adolescents usually exhibit late sleep phase and irregular sleep patterns. As a result, they do not get enough sleep and report daytime sleepiness. This condition could be aggravated in working students who have a more limited time for sleep. In this survey, we investigated the impact of evening classes and employment on the sleep patterns of adolescents. We compared female (n = 17) and male (n = 14) non-worker students to female (n = 28) and male (n = 20) worker students who attended the same high school. The volunteers (aged 17.4 years +/- 11 months) answered a sleep log during a 16-day period. Worker students slept and woke up earlier, had a shorter nocturnal sleep length and a shorter daily (nocturnal plus diurnal) sleep length compared to non-working pupils. The four groups of students delayed sleep onset time on weekends, but only worker students delayed wake-up time on Sundays. The wake-up time was similar among groups on Sundays. While student workers tended to increase the sleep length in the weekends, non-working students increased it on Mondays and/or Tuesdays. The results showed that sleep schedules and sleep length were different according to the work status. Going to bed later on Saturday by the four groups of students suggests the influence of social activities, while a later wake-up time on Sundays could result from a shorter sleep length on workdays.
Keywords: sleep-wake cycle; adolescence; adolescent labor; biological rhythm